Analisis Kesalahan Peserta Didik dalam Menyelesaikan Masalah Peluang Berdasarkan Newman's Error Analysis Ditinjau dari Kemampuan Literasi Digital - Della Aulia (Fakultas Perguruan dan Ilmu Pendidikan, 2026)
This study aims to analyze students’ errors in solving probability problems based on Newman’s Error Analysis in terms of digital literacy skills. The research employed a descriptive qualitative approach involving tenth-grade students of SMA Negeri 5 Jember in the 2025/2026 academic year. The research subjects were selected using purposive sampling based on three categories of digital literacy levels: high, medium, and low. The research instruments consisted of a digital literacy questionnaire, a digital-based test on mutually exclusive probability events, and interview guidelines to explore students’ thinking processes in greater depth. The digital literacy questionnaire was developed based on the indicators of internet searching, hypertextual navigation, content evaluation, and knowledge assembly. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing using triangulation techniques involving questionnaire results, test results, and interview data to ensure the validity and depth of the findings. The findings revealed that students with high digital literacy tended to make errors in the transformation stage and final answer writing stage. Although these students were able to read and understand the problems well, they were still less systematic in transforming problem information into mathematical models and often failed to provide complete final conclusions. Students with moderate digital literacy tended to experience errors in the comprehension, transformation, and final answer writing stages due to a lack of accuracy in interpreting information presented in digital-based problems. Meanwhile, students with low digital literacy demonstrated more varied errors, including comprehension, transformation, process skills, and final answer writing errors. These findings indicate that digital literacy significantly influences students’ ability to understand information, process data, and solve digital-based mathematics problems. Therefore, integrating digital literacy into mathematics learning is essential to help students think more systematically and critically while minimizing errors in solving mathematical problems.
Finalisasi Juli 2026 hasyim
Keywords: digital literacy; newman’s error analysis; probability